Effects of essential fatty acids deficiency in milk diets on the development of germ-free and conventional rats - Stĕpánková, R; Dvorák, B; Sterzl, J; Trebichavský, I (Physiologia Bohemoslovaca, 1990)
Conditions allowing physiological development were determined in infant rats delivered by Caesarian section on the 22nd day of gestation and fed, from birth onwards, on various diets by stomach tube. Two new diets were prepared--K 50 A (11.7% fat, 7.7% protein) and LNaH (7.6% protein, 12% fat). The sole difference between the two diets is in the essential fatty acid (EFA) content, which is 42.6% in diet K 50 A, but only 0.7% in diet LNaH. Animals reared on the LNaH diet displayed slower growth and delayed development of the adenohypophysis and the thymus. Degenerative changes (intracytoplasmic vacuolation) were found in the somatotropin-producing cells of the adenohypophysis. The serum prolactin concentration of animals fed on the LNaH diet was lower than in the suckled controls and in animals given the K 50 A diet. The damaging effect of the LNaH diet was particularly marked on the first five days after birth, indicating that this is a critical period in the development of the newborn rat. The histological structure of the adenohypophysis and thymus of animals reared on the K 50 A diet was the same as in the suckled controls.
Keywords: Organ Size; Animals, Newborn; velikost orgánu; Thymus Gland; plíce; Animals; tělesná hmotnost; prolaktin; Body Weight; gnotobiologické modely; thymus; Prolactin; novorozená zvířata; Fatty Acids, Essential; krysa rodu Rattus; dietní tuky; Rats; Liver; esenciální mastné kyseliny; mozek; zvířata; Germ-Free Life; Pituitary Gland, Anterior; adenohypofýza; Dietary Fats; Brain; inbrední kmeny potkanů; játra; Rats, Inbred Strains; Lung